Mengoptimalkan Platform Media Sosial untuk Mendorong Keterlibatan Aktif Masyarakat dalam Mengatasi Perubahan Iklim dan Pelestarian Lingkungan - Rina Lestari; Achmad Nurmandi; Muhammad Younus; Herman Lawelai; Wahdania Suardi (Society, 2025)
This research aims to optimize social media platforms to foster active public engagement in tackling climate change and environmental conservation. Social media enables rapid and widespread dissemination of information, creates space for public discussion, and encourages collective action on environmental issues. In this study, researchers applied a qualitative method with a systematic literature review approach, using bibliometric analysis using the Scopus database. The analysis results show a significant increase in publications related to this topic from 2019 to 2024, reflecting the important role of social media in climate change mitigation efforts. With interactive features such as hashtags and online campaigns, social media strengthens awareness and collaboration across communities, governments, and the private sector. In addition, social media plays a role in building digital communities that support each other in promoting environmentally friendly behaviors. The study also highlights the importance of managing accurate information to avoid disinformation and maximize the positive impact of digital platforms on sustainable environmental policy advocacy.